Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1002/(sici)1097-0142(19970601)79:11<2137::aid-cncr11>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Response to second-line chemotherapy in patients with metastatic breast carcinoma previously responsive to first-line treatment

Abstract: Retained chemosensitivity appeared to be an important characteristic in patients responding to second-line chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…1 Liver metastasis is found in about 15% of patients with metastatic breast cancer, 2 but only 4%-5% of these patients present with isolated liver metastasis. 2,3 Thus, the dissemination of disease to other sites usually contraindicates liver resection.…”
Section: Introductionmentioning
confidence: 99%
“…1 Liver metastasis is found in about 15% of patients with metastatic breast cancer, 2 but only 4%-5% of these patients present with isolated liver metastasis. 2,3 Thus, the dissemination of disease to other sites usually contraindicates liver resection.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, recurrence of hormone receptor-negative disease may be treated with single-agent, sequential chemotherapy, or combination chemotherapy [1]. If recurrence of hormone receptor-negative disease occurs many years after administration of adjuvant anthracycline-and taxane-containing chemotherapy, re-treatment with drugs within these classes may still remain an appropriate treatment choice [6]. If recurrence occurs within a year of this adjuvant treatment, other chemotherapy classes would generally be preferable.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, 6 studies found that patients with a response and/or longer TTP or PFS of previous chemotherapy also had longer TTP or PFS on next-line chemotherapy. [84][85][86][87][88][89][90] Additionally, the median PFS of 11 months for second-line chemotherapy measured in the study by Brun et al 90 is long compared with the other studies evaluating second-line chemotherapy (Figure 7.2B). This might be explained by the fact that this study only selected patients who had a complete or partial response to first-line chemotherapy, supporting this notion of a possible prognostic role for response to previous-line chemotherapy for the length of next-line PFS.…”
Section: Multiple Chemotherapy Lines In Clinical Practice: Number Of ...mentioning
confidence: 83%
“…A remarkable finding was the significant association between outcomes from previous chemotherapy regimens and outcomes of next-line chemotherapy described in 6 real-world studies. [84][85][86][87][88][89][90] Furthermore, response to previous chemotherapy 88,89,94,111,112 and longer PFS 84,93,113 was described to significantly increase OS in observational trials. The relationship between PFS and OS was also seen within approval studies of chemotherapy and previously described in a systematic review specifically focusing on first-line (mean ratio of median PFS: median OS of 1/3).…”
Section: Discussionmentioning
confidence: 99%